Dividend Policy Models and Possibilities of Their Utilization in the Conditions of a Particular Country – Assessment and Proposals - Bělušová, Kristýna; Brychta, Karel (University of Hradec Králové, 2021)
The aim of this paper is to describe and compare the existing models of the dividend policy and consequently to present general considerations related to the establishment of a dividend policy model for a particular country (when presenting some specific features for the Czech Republic). The comparison presented in this paper includes 18 existing dividend policy models. Based on the analysis, it may be stated that the models can be divided into two basic groups. The first category of models is aimed at assessing the effect of tax rates on the dividend policy. The second category of models aims at determining the factors affecting the dividend policy. A number of common considered factors may be identified in all the examined models, such as the tax rate on dividends and capital gains, profit/profitability, or debt ratios. Based on the synthesis of the knowledge gained, the authors identified several categories of variables that shall be taken into consideration when creating a dividend policy model for a particular country, namely: general categories aimed at general description of the subject, profitability indicators, indicators of indebtedness, cash and liquidity indicators, assessment of investment opportunities, ownership indicators, tax aspects indicators and relevant category variables.

The aim of this paper is to describe and compare the existing models of the dividend policy and consequently to present general considerations related to the establishment of a dividend policy model for a particular country (when presenting some specific features for the Czech Republic). The comparison presented in this paper includes 18 existing dividend policy models. Based on the analysis, it may be stated that the models can be divided into two basic groups. The first category of models is aimed at assessing the effect of tax rates on the dividend policy. The second category of models aims at determining the factors affecting the dividend policy. A number of common considered factors may be identified in all the examined models, such as the tax rate on dividends and capital gains, profit/profitability, or debt ratios. Based on the synthesis of the knowledge gained, the authors identified several categories of variables that shall be taken into consideration when creating a dividend policy model for a particular country, namely: general categories aimed at general description of the subject, profitability indicators, indicators of indebtedness, cash and liquidity indicators, assessment of investment opportunities, ownership indicators, tax aspects indicators and relevant category variables.
Dividend Policy Models and Possibilities of Their Utilization in the Conditions of a Particular Country – Assessment and Proposals
Keywords: Czech Republic; dividend policy; dividend policy models; establishing dividend policy model; Czech Republic; dividend policy; dividend policy models; establishing dividend policy model